Guidance manual for the valuation of regulating services (UNEP NairobiKE, 2010)
This manual explores methods and necessary tools for valuing regulating ecosystem servics. It explains the concept and methodology involved. The clarity in methodological steps, combined with rich issulstrations, should prove an asset for practitioners and end users alike.
Keywords: ECOSYSTEMS